Identifying small molecules for protecting chondrocyte function and matrix integrity after controlled compressive injury - Saleh Al Jundi; Jerahme R. Martinez; Jake Cresta; Farzad Yousefi; Gabriel DeSantis; Matthew Thoonkuzhy; Emilie Rabut; Bhavana Mohanraj; Robert L. Mauck; George R. Dodge (Osteoarthritis and Cartilage Open, 2022)
Objective: Articular cartilage injury is central for the development of post-traumatic osteoarthritis (PTOA). With few disease-modifying therapies successful at offsetting progressive osteoarthritis (OA), our goal is to use a high throughput screening platform of cartilage injury to identify novel chondroprotective compounds. Targeting articular cartilage damage immediately after injury remains a promising therapeutic strategy to overcome irreversible tissue damage. Method: We constructed a single impact-cartilage screening method using a multi-platen system that simultaneously impacts 48 samples and makes use of engineered cartilage tissue analogs (known as CTAs). Drug libraries were screened and assessed for their ability to alter two crucial biological responses to impact injuries, namely matrix degradation and cell stress. Results: Over 500 small molecules were screened for their ability to alter proteoglycan loss, matrix metalloproteinase activity, and cell stress or death. Fifty-five compounds passed through secondary screening and were from commercial libraries of natural and redox, stem cell related compounds, as well as protease, kinase and phosphatase inhibitors. Through secondary screening, 16 promising candidates exhibited activity on one or more critical function of chondrocytes. While many are mechanistically known compounds, their function in joint diseases is not known. Conclusion: This platform was validated for screening drug activity against a tissue engineered model of PTOA. Multiple compounds identified in this manner have potential application as early protective therapy for treating PTOA, and require further study. We propose this screening platform can identify novel molecules that act on early chondrocyte responses to injury and provide an invaluable tool for therapeutic development.